1993
DOI: 10.1111/j.1365-2222.1993.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine mast cells attach to and migrate on laminin‐, fibronectin‐, and matrigel‐coated surfaces in response to FcεRI‐mediated signals

Abstract: We have examined the possibility that mouse bone marrow-derived cultured mast cells (BMCMC) have the capacity to attach to and migrate on extracellular matrix components in vitro through the use of time lapse videography. Unactivated mast cells did not display significant interaction with slide flasks coated with either 3% BSA or collagen IV, and Fc epsilon RI-mediated activation of BMCMC did not appreciably increase their attachment and migratory characteristics. Both activated and unactivated BMCMC adhered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Mast cell activation of Fc⑀RI receptor stimulates an increase in cell adhesion, and this adherence is required to facilitate localized synthesis of cytokines (19,20). Given the role of Paks in cell migration, adhesion, and cytoskeleton regulation, we sought to discover a role for Paks in mast cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Mast cell activation of Fc⑀RI receptor stimulates an increase in cell adhesion, and this adherence is required to facilitate localized synthesis of cytokines (19,20). Given the role of Paks in cell migration, adhesion, and cytoskeleton regulation, we sought to discover a role for Paks in mast cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Mast cells also display increased motility upon activation of FcεRI and Kit signaling (27,54,64). Since we observed reduced p38 activation in fer DR/DR BMMCs (Fig.…”
Section: Dr/drmentioning
confidence: 96%
“…However, the aggregation of FcεRI is required for degranulation and release of lipid mediators. Mast cell activation downstream of either FcεRI or the Kit receptor also leads to increased cell adhesion (13,53) and increased cell motility (54,64). The activation of p38 MAP kinase is critical for both antigen-dependent mast cell migration via FcεRI (27) and chemotaxis upon Kit receptor activation (59).…”
mentioning
confidence: 99%
“…It was reported that bone marrow-derived mouse mast cells adhere to laminin and fibronectin and that this adherence is induced by Fc⑀RI-mediated signals and SCF. 12,13 Studies in humans showed that mast cells from uterus and lung express the ␤1 integrins ␣4␤1 and ␣5␤1, known as receptors for fibronectin, and that skin mast cells adhere to fibronectin and laminin. [14][15][16] The immature human mast cell line (HMC)-1 also expresses ␣2␤1, ␣3␤1, ␣6␤1, ␣V␤1, ␣V␤5, and CD44.…”
mentioning
confidence: 99%